Philosophy of science : a beginner's guide - Gorham, Geoffrey (Oneworld, 2011)
The world didn't end on 10 September 2008, but the possibility may have got you thinking: was it worth the risk? What is the point of science actually? Geoffrey Gorham considers these questions and explores the social and ethical implications of science by linking them to issues facing scientists today: human extinction, extraterrestrial intelligence, space colonization, and more.